The Image of Women in the Poetry of The Marsinah Fall by Sapardi Djoko Damono - Muhammad Aditya Wisnu Wardana; Chafit Ulya (Pioneer: Journal of Language and Literature, 2021)
The poem Dongeng Marsinah by Sapardi Djoko Damono is one of the literary works that comes with an approach to the study of feminism and the image of women to respond to people's lives today. The data collection technique uses document analysis based on feminist literary theory. The interesting thing in the poem entitled Dongeng Marsinah by Sapardi Djoko Damono is the emergence of a women's movement against injustice or patriarchy through a literary work. The theory used is based on feminism literary theory with a sociological approach to literature. The view of literary works in the poem entitled Dongeng Marsinah by Sapardi Djoko Damono has a reflection on today's social life. The representation of women in the poem Dongeng Marsinah by Sapardi Djoko Damono include: (1) the representation of women from a psychological perspective; (2) the representation of women in society; (3) the representation of women in terms of behavior; and (4) the representation of women from a physical point of view. The hope is that by understanding the meaning of the image of women in the poem, a woman should not be treated with violence physically, mentally, or sexually.